Differences in retinal neovascular tissue and vitreous humour in patients with type 1 and type 2 diabetes. Issue 8 (19th March 2009) - Kinnunen, K; Puustjärvi, T; Teräsvirta, M; Nurmenniemi, P; Heikura, T; Laidinen, S; Paavonen, T; Uusitalo, H; Ylä-Herttuala, S
Abstract : Aims: The aim of the study was to evaluate the histopathology of neovascular tufts and vitreous samples collected from patients with diabetes. Methods: Vitreous samples and neovascular tufts were collected from patients with type 1 (n = 13) and (n = 17) type 2 diabetes with proliferative retinopathy, and from controls with a macular hole (n = 5). Neovessels were analysed using immunohistochemistry and vitreous samples with an enzyme-linked immunosorbent assay (ELISA). The main outcome measure was to examine differences in the levels of growth factors in patients with type 1 and type 2 diabetes with proliferative retinopathy. Results: Vascular endothelial growth factor (VEGF)-A was most strongly present in the samples from patients with type 1 diabetes. In type 2 diabetes, VEGF-D was more abundantly present than in type 1 diabetes. Angiopoietin (ANG)-2 was also abundantly present. Macrophages and nuclear factor kappa B (NFκB) were found, indicating the presence of an inflammatory process in the neovascular tissues. Conclusions: VEGF-A and ANG-2 are equally important in the neovascular process in both type 1 and type 2 diabetes. VEGF-D is abundantly present in type 2 diabetes. In order to achieve better control of diabetic retinopathy, it might be beneficial to develop treatments that prevent the actions of ANG-2 and VEGF-D.